Clinical Validation of Natural Plant Based Skincare Supplement in Healthy Subjects - Dr. Vidyadhar Kumbhar,; Dr. Veena Deo,; Ankush Chourasia,; Dr. Gayatri Ganu,; Dr. Rupali Mali, (International Journal of Innovative Research in Medical Science, 2021)
Background: The growing field of psycho-dermatology is all about the mind-skin connection. It addresses the link between our emotional state, the body’s physiological response to our emotional state, and the outcome of this response on our skin, body, health, and well-being. The aim of this clinical trial is to evaluate safety and efficacy of BP-G01 in improving skin health, complexion and skin luster. Material and methods: Total 33 subjects were screened and out them 3 were considered as drop outs and 30 completed subjects were involved in the study. Natural plant based skincare supplement (BP-G01) contains Plant based protein blend like Plant proteins like rice and pea proteins. The glow blend like evening primrose extract, pearl powder, orange, pomegranate, grape seed extract, sea buckthorn extract and tocopherols from plant source. The adaptogenic blend like Ashwagandha, Amla, Tulsi, Mulethi and Turmeric extracts. It was consumed as 90 days’ treatment in dose of 20 gm in the morning after breakfast or post workout with 200 ml of water or milk. Natural plant based skincare supplement (BP-G01) improve improved skin luminosity, brightness, radiance and complexion, skin hydration, skin discoloration, dark circles, dark spots from face and neck and skin evenness indicated by MASI scoring for reducing hyper pigmentation, dark spots/ circles and redness and reduction in mild acne counts. VAS for the improvements in skin complexion and evenness. C.L.B.T. imperfections scale. Result: There was 17.08, 22.79, 32.56 and 37.96% reduction in the MASI score at day 15, 30, 60 and day 90 respectively by reducing hyper pigmentation, dark spots/ circles and redness by MASI scoring. MASI acne score at baseline was 9.10 ± 1.19 which was decreased throughout the period of treatment by reduction in mild acne counts as per modified MASI scoring. Conclusion: BP-G01 is safe and effective in promoting skin health in healthy adults.